2022
DOI: 10.1101/2022.09.25.509411
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increase the flow rate and improve hydrogen deuterium exchange mass spectrometry

Abstract: Reversed-phase peptide separation in hydrogen deuterium exchange (HDX) mass spectrometry (MS) must be done with conditions where the back exchange is the slowest possible, the so-called quench conditions of low pH and low temperature. To retain maximum deuterium, separation must also be done as quickly as possible. The low temperature (0 &degC) of quench conditions complicates the separation and leads primarily to a reduction in separation quality and an increase in chromatographic backpressure. To improve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In comparison to the results obtained in the microchip electrophoresis study, 16 our UDMS E identifications found three of the six peptides reported in that paper. A very recent report using higher than normal LC flow rates has reported achieving peak capacities of 59.6 in a 10 min gradient using 200 μL/min flow rates, 15 and while this is an improvement over the LC separation reported in Table 1, it is still below the capacity attainable on CE tested in this study and elsewhere. 16 Back Exchange and Carryover.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to the results obtained in the microchip electrophoresis study, 16 our UDMS E identifications found three of the six peptides reported in that paper. A very recent report using higher than normal LC flow rates has reported achieving peak capacities of 59.6 in a 10 min gradient using 200 μL/min flow rates, 15 and while this is an improvement over the LC separation reported in Table 1, it is still below the capacity attainable on CE tested in this study and elsewhere. 16 Back Exchange and Carryover.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The main drawbacks of these systems are their cost, and due to the low temperatures, high backpressures (up to ∼20,000 psi) because of increased mobile phase viscosity, and reduced separation efficiency of LC (a result of resistance of mass transfer). 15 , 16 This resistance to mass transfer not only degrades the separation efficiency of LC but also results in an increased risk of carryover of injected material from prior injections as the interaction between peptides and protease, trap, and analytical column stationary phase becomes more difficult to disrupt. The carryover of material is detrimental to HDX experiments as retained peptides lose deuterons as they are exposed to 100% H 2 O solvents, only to then elute during subsequent separations, confounding the apparent uptake kinetics.…”
mentioning
confidence: 99%
See 1 more Smart Citation